Crystal structure of methyltriphenylphosphonium iodide, C19H18IP - Hosten Eric; Gerber Thomas; Betz Richard (Zeitschrift für Kristallographie - New Crystal Structures, 2012)
C19H18IP, monoclinic, P21/c (no. 14), a = 9.0703(3) Å, b = 19.0974(6) Å, c = 11.9927(3) Å, β = 120.079(2)°, V = 1797.7 Å3, Z = 4,Rgt(F) = 0.0197, wRref(F2) = 0.0464, T = 200 K.